Clinical Course and Outcome of 12 Breast TB Cases - Debi, R; Sarker, BC; Chowdhury, S; Khan, MMR; Basak, PM; Das, Tapash Ranjan (TAJ: Journal of Teachers Association, 2018)
Breast TB is a very rare form of extrapulmonary TB. So, case reviews are also less common. 12 breast TB cases diagnosed and treated between June 2011- June 2014 in the private chamber were retrospectively reviewed. All cases were female, their mean age was 34.4 years. All were new cases and only one had pulmonary TB. Patients presented with hard, irregular breast lump (83.3%), swelling of the breast (25%), secretion from the involved breast (33.3%), breast pain (50%). Montaux test was negative in 83.3% patients and chest x-ray findings was positive only in one case. ESR was raised and FNAC showed granulomatous changes in all cases. All received Directly Observed Treatment Short Course regimen for a duration of 6 months. Segmental resection was not done. Small lump persisted in only 2 eases after treatment. From the above findings it can be said that breast TB should be considered as a differential diagnosis of breast neoplasia and it can be successfully treated by anti-TB drugs. TAJ 2013; 26: 24-26